Predictors of acute symptomatic seizure in cerebral venous thrombosis patients—a multicenter cohort study - Naaem Simaan; Jeremy Molad; Hen Hallevi; Issa Metanis; Rom Mendel; Rani Barnea; Eitan Auriel; Jonathan Naftali; Ruth Eliahou; Shorooq Aladdin; David Orion; Shlomi Peretz; et al. (Therapeutic Advances in Neurological Disorders)
Background: Acute symptomatic seizures (ASYS) is a common presentation in cerebral sinus venous thrombosis (CSVT) patients. Objectives: We aimed to characterize CSVT patients experiencing ASYS within 7 days from presentation. Additionaly, we aimed to find predictors for ASYS within CSVT patients. Methods: Prospective CSVT databases from six academic centers (January 2010–December 2023) were retrospectively analyzed. Clinical outcomes at the 90-day follow-up included seizure occurrence and the modified-Rankin-Scale (mRS). Results: From 529 included patients (mean age 42.4 ± 18.6 years, 64.3% females), 106 (20%) had ASYS. ASYS patients were more often males (47.2% vs 20.1%, <0.001), and presented more often with focal neurological deficits (50% vs 22%, p  < 0.001) but less often with papilledema (13.2% vs 29.3%, p  < 0.001). On multivariate analysis cortical-vein thrombosis (odds ratio (OR) 4.17, p  < 0.001), intracerebral hemorrhage (ICH; OR 3.06, p  = 0.002), any superior-sagittal-sinus (SSS) thrombosis (OR 2.49, p  = 0.006), predicted ASYS. Conversely, presentation with papilledema (OR 0.39, p  = 0.03) negatively predicted ASYS. ASYS patients had lower rates of 90-day-mRS-0-1 (51.9% vs 83.9%, p  < 0.001). Patients who experienced seizures between the second and seventh day (n = 58) had similar baseline characteristics to those with seizures only on the day of presentation (n = 48) but were less likely to achieve a good functional outcome by day 90 (42.6% vs 58.9%, p  < 0.05) and had a lower rate of complete recanalization on follow-up venous imaging (25.5% vs 57.5%, p  = 0.02). Status-epilepticus in comparison to non-ASYS patients achieved lower rates of 90-day-mRS-0-1 (11% vs 84%, p  < 0.001) and higher 90-day-mortality (44% vs 5.6%, p  < 0.001). In a multivariate analysis ASYS was a negative predictor for 90-day-mRS-0-1 (OR 3.3, 95% confidence interval 1.43–7.5, p  = 0.005). Conclusion: CSVT patients experiencing ASYS, and to a greater degree patients with either status epilepticus or ASYS between second and seventh day achieved less often 90-day-mRS-0-1. Possibly, they epitomize a different course of disease that may require a more suitable treatment strategy.